Institutional investors, corporate governance, and earnings management around merger: Evidence from French absorbing firms - Njah, Mouna (2013)
This paper examines the association between institutional ownership and the earnings management beha-vior of some French absorbing firms. Using a sample of 76 French mergers and absorptions concluded over the period ranging from 2000 to 2010, we undertake to present some empirical evidence highlighting that absorbing-firms manipulate earnings relevant to the year preceding the merger-offer in the presence of institutional cross-holding. However, the presence of active institutions turns out to limit the managerial accruals discretion. The monitoring role exerted by the active-institutional investors does restrict the oppor-tunities of earnings management around mergers and acquisitions. Further analyses suggest that the average value of discretionary accruals with regards to the absorbing firms proves to be influenced by the nature of merger deal (takeover vs. restructuring).